PERANAN PENYULUH PERTANIAN LAPANGAN (PPL) TERHADAP KEBERHASILAN PROGRAM PENGEMBANGAN USAHA AGRIBISNIS PEDESAAN (PUAP) DI KECAMATAN SUNGKAI SELATAN, KABUPATEN LAMPUNG UTARA - Riyando Ardika Aria; Tubagus Hasanuddin; Rio Tedi Prayitno (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2016)
The purpose of this study are to analyzethe success level of PUAP program, the level of the AEW’roles on PUAP program, and the factors  related to the success of the PUAP program.  This research was conducted in Sungkai District of North Lampung Regency.  The samples are 52 farmers selected randomly and 12 Agricultural Extension Workers selected purposively.  The data analysis methods used are qualitative-descriptive analysis, tabulation, and Rank Spearman correlation.  The results showed that the PUAP program has been successful, inrelation to output, outcome, benefit, and impact.The level of AEW’sroles towards the success of PUAP program was in good category, in the roles as the diseminator of information/inovation, facilitator, supervisor, monitoring, and evaluator. The factors related to the successof PUAP Program were the level ofAEW’sroles, the level of farmer’s participation, the level of managementfunds received by farmers, and farmers' level of knowledge about PUAP program.Key words: Agricultural Extension Worker,PUAP program, role, success